AN ANALYSIS OF THE EMERGING FACTORS OF FLA AND FLE BASED ON STUDENTS' PERCEPTION - Maula Khoirunnisa; Yazid Basthomi; Mirjam Anigerahwati (Universitas Negeri Malang, 2020)
Abstract: This qualitative survey study investigated the students' perspectives on the emerging factors of anxiety and enjoyment during ESP class of non-English department students. This study involved 35 freshmen of non-English department study program at Universitas Muhammadiyah Malang who were joining ESP class. The most frequent causes of FLA based on the students' perception were being afraid that their utterances are not understandable, their own concern on their pronunciation and accent and thoughts that others can speak better than they do. For FLE, the excellent atmosphere created by the teachers was most considered by the students to contribute to their enjoyment in class.  Keywords: anxiety, enjoyment, ESP, FLA, FLE Abstrak: Penelitian yang menggunakan metode survey kualitatif ini menggali tentang perspektif mahasiswa di luar jurusan Bahasa Inggris tentang kecemasan (FLA) dan perasaan senang (FLE) dalam mengikuti kelas ESP. Penelitian ini melibatkan 35 mahasiswa yang bukan jurusan Bahasa Inggris di Universitas Muhammadiyah Malang yang mengikuti kelas ESP. Penyebab FLA yang paling sering terjadi berdasarkan persepsi mahasiswa adalah ketakutan bahwa ucapan mereka tidak dapat dimengerti, rasa cemas pribadi terhadap pengucapan dan aksen mereka serta pemikiran bahwa orang lain dapat berbicara lebih baik daripada mereka. Untuk FLE, suasana baik yang diciptakan oleh para guru menjadi sebuah perhatian khusus yang dirasa oleh para mahasiswa untuk menambah rasa senang mereka di kelas. Kata kunci: kecemasan, kesenangan, ESP, FLA, FLE